Introducing robustness in DBR routing protocol. (28th February 2020) - Mahmood, Tariq; Akhtar, Faheem; Rehman, Khalil Ur; Azeem, Muhammad; Mudassir, Azhar Imran; Daudpota, Sher Muhammad
Exploration of advanced technologies employed for streamlining UWSN devices is a hot issue. Challenges faced by UWSN are high power consumption, increased propagation latency and dynamic topology of nodes. Depth-based routing protocols are designed to cope these challenges that use depth information to forward data toward surface sink. Depth-based routing and energy efficient depth-based routing are widely used routing protocols in UWSN. DBR has low stability period due to un-necessary data forwarding and high load on mid and low-depth nodes. In DBR quick energy consumption of nodes creates large holes in the network. The path connectivity hole leads retransmission of packets that consumes excessive energy, route-update cost and end-to-end delay. In this paper, the proposed robust depth-based routing protocol is used to overcome deficiencies of DBR by limiting number of forwarding nodes considering variation in depth-threshold, holding-time and distance-differences to minimise end-to-end delay.